2009
DOI: 10.1210/er.2008-0025
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Roles in Spermatogenesis and Fertility: Lessons from Testicular Cell-Specific Androgen Receptor Knockout Mice

Abstract: Androgens are critical steroid hormones that determine the expression of the male phenotype, including the outward development of secondary sex characteristics as well as the initiation and maintenance of spermatogenesis. Their actions are mediated by the androgen receptor (AR), a member of the nuclear receptor superfamily. AR functions as a ligand-dependent transcription factor, regulating expression of an array of androgen-responsive genes. Androgen and the AR play important roles in male spermatogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
271
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(298 citation statements)
references
References 128 publications
(173 reference statements)
11
271
4
4
Order By: Relevance
“…The lack of AR immunoreaction for spermatogonial subtypes is also consistent with previous reports (Bremner et al, 1994;Vornberger et al, 1994;Matsumiya et al, 1999). AR functions as a ligand-dependent transcription factor, since ligand binding is a prerequisite for its transport to the nucleus where it accesses and regulates an array of androgen-responsive genes (Georget et al, 1997;Wang et al, 2009). The regulation of AR functionality is far from being understood but their cytoplasmic localization has been usually interpreted as an inactivated state (Tyagi et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lack of AR immunoreaction for spermatogonial subtypes is also consistent with previous reports (Bremner et al, 1994;Vornberger et al, 1994;Matsumiya et al, 1999). AR functions as a ligand-dependent transcription factor, since ligand binding is a prerequisite for its transport to the nucleus where it accesses and regulates an array of androgen-responsive genes (Georget et al, 1997;Wang et al, 2009). The regulation of AR functionality is far from being understood but their cytoplasmic localization has been usually interpreted as an inactivated state (Tyagi et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…It is known that androgens and their cognate receptors are critical in determining the male phenotype and their roles in spermatogenesis have been widely investigated (Ghosh et al, 1991;O'shaughnessy et al, 2002;Yeh et al, 2002;Tsai et al, 2006;Wang et al, 2009). On the other hand, there is little information concerning the influence of androgen/AR signaling on germ cell differentiation during the fetal and neonatal periods.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, recent studies have shown that steroids, such as oestradiol-17b, testosterone and progesterone, can inhibit the transport activity of Bcrp and upregulate Bcrp expression and its cellular localisation in cancer cells, endothelial cells of the brain and endocrine organs. 21,41,42 Steroids, particularly testosterone and oestrogens, are known to regulate BTB and testicular Bcrp and spermatogenesis XJ Qian et al 456 function, [43][44][45][46] and Bcrp plays a significant role in regulating the transport of steroids across the myoid cells and Sertoli cells at the apical ES (Table 1). Additionally, the activity, expression and cellular distribution of Bcrp are regulated by steroids.…”
Section: Substratesmentioning
confidence: 99%
“…The gene expression levels of AR reflect the reproductive function of the rat (18)(19)(20). Therefore, the localization and quantitative analysis of AR was performed using immunological assays.…”
Section: Localization and Quantitative Expression Of Androgen Receptormentioning
confidence: 99%